Pustular Psoriasis Induced by Dupilumab: A Case Report - Liu Y; Liu L; Zhou H; Chen G; Wen C; Wu R (Dove Medical Press, 2024)
Yuetong Liu,1,* Lanxin Liu,1,* Hongmei Zhou,2 Guangfang Chen,2 Changhui Wen,2 Ran Wu2 1Guizhou University of Traditional Chinese Medicine, Guiyang, Guizhou, 550002, People's Republic of China; 2Department of Dermatology, The First Affiliated Hospital of Guizhou University of Traditional Chinese Medicine, Guiyang, Guizhou, 550001, People's Republic of China*These authors contributed equally to this workCorrespondence: Ran Wu, Department of Dermatology, The first affiliated hospital of Guizhou University of Traditional Chinese Medicine, Guiyang, Guizhou, 550001, People's Republic of China, Email wuranshou@126.comAbstract: Atopic dermatitis (AD) and psoriasis (Pso) are both recurrent inflammatory diseases. Recently, it has been reported that a small number of AD patients experience immune drift after receiving dupilumab treatment, leading to a transition from eczema-like lesions to psoriasis-like lesions. Here, we report a case of pustular psoriasis caused by dupilumab treatment for atopic dermatitis. This case underscores the diagnostic challenges associated with immune drift related to biological agents while also highlighting the shortened time frame for immune drift onset compared to previous reports.Keywords: immune drift, dupilumab, atopic dermatitis, pustular psoriasis